The Influence Of Earnings Management, Audit Quality On Company Value With Ownership Managerial As Moderating Variables - Sri Ayem; Wihelmina Menge (INVOICE : JURNAL ILMU AKUNTANSI, 2022)
This study aims to examine the effect of earnings management and audit quality on firm value with managerial ownership as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The independent variable used is earnings management which is proxied using the modified Jones model and audit quality is measured using a dummy variable with the dependent variable being firm value as measured by price to book value (PBV). This study adds a moderating variable, namely managerial ownership. The population in this study are manufacturing sector companies listed on the IDX for the 2016-2019 period. The method of determining the sample is done by using purposive sampling. Based on these criteria, as many as 24 companies were selected as samples. The data analysis technique used in this study is multiple regression analysis and moderated regression analysis using SPSS 21 software. The results of this study indicate that earnings management variables have a negative effect on firm value while audit quality also has a negative effect on firm value. The results of the study using a moderated regression analysis test showed that managerial ownership was able to strengthen the relationship between earnings management and firm value. Managerial ownership is also able to strengthen the relationship between audit quality and firm value.